EXPLOITING THE TRANSIENT RESPONSE OF A SINGLE DEGREE-OF-FREEDOM OSCILLATOR FOR THE PURPOSE OF ENERGY HARVESTING - Gatti, Gianluca; Brennan, Michael J. [UNESP]; Crocker, M. J.; Pawelczyk, M.; Pedrielli, F.; Carletti, E.; Luzzi, S. (Int Inst Acoustics & Vibration, 2015)
Vibration-based energy harvesters have been intensively studied recently because of the need to power wireless devices or to augment the use of batteries. When time-unlimited harmonic excitation is provided to a single degree of freedom oscillator, good performance is achieved if the device is tuned to the excitation frequency. In such a situation, the harvested energy is inversely proportional to the suspension damping, which is thus sought to be very low. However, for time-limited excitation very low damping involves relatively long transients, both at the beginning and at the end of the response, which can affect the harvesting performance considerably. This paper presents an investigation on the design of a linear spring-mass-damper system to scavenge energy from time-limited oscillations, which could be a more likely situation in some practical applications, compared to a state-state assumption.